2018
DOI: 10.12809/hkmj177007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a multiplex flow immunoassay versus conventional assays in detecting autoantibodies in systemic lupus erythematosus

Abstract: In a local lupus cohort, BioPlex showed comparable sensitivity to indirect immunofluorescence in detecting ANAs and comparable performance to ELISA in detecting anti-ENA antibodies. However, CIEP was the best method in terms of disease specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
(31 reference statements)
1
4
0
1
Order By: Relevance
“…Automated Phadia® 250 for the detection of anti-ENAs showed comparable performance with conventional microplate ELISA in that the two methods showed overall good analytical agreement and that the diagnostic performance showed no statistically significant differences, except for anti-RNP and anti-Sm. Although there are no evaluation reports comparing the exact same methods of FEIA and ELISA in detecting anti-ENAs, our results are in line with a recent study comparing FEIA methods with enzyme immunoassays (EIA) and with a study comparing multiplexed flow immunoassay with conventional ELISA assay 1213. In the previous study comparing EIA-based assay with FEIA, the two showed good agreement (kappa coefficient=0.70), and regarding clinical implications, the two showed comparable results 12.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Automated Phadia® 250 for the detection of anti-ENAs showed comparable performance with conventional microplate ELISA in that the two methods showed overall good analytical agreement and that the diagnostic performance showed no statistically significant differences, except for anti-RNP and anti-Sm. Although there are no evaluation reports comparing the exact same methods of FEIA and ELISA in detecting anti-ENAs, our results are in line with a recent study comparing FEIA methods with enzyme immunoassays (EIA) and with a study comparing multiplexed flow immunoassay with conventional ELISA assay 1213. In the previous study comparing EIA-based assay with FEIA, the two showed good agreement (kappa coefficient=0.70), and regarding clinical implications, the two showed comparable results 12.…”
Section: Discussionsupporting
confidence: 88%
“…Although there are no evaluation reports comparing the exact same methods of FEIA and ELISA in detecting anti-ENAs, our results are in line with a recent study comparing FEIA methods with enzyme immunoassays (EIA) and with a study comparing multiplexed flow immunoassay with conventional ELISA assay. 12,13 In the previous study comparing EIA-based assay with FEIA, the two showed good agreement (kappa coefficient=0.70), and regarding clinical implications, the two showed comparable results. 12 In a study comparing FEIA with conventional indirect immunofluorescence assay, the percent agreement between the two assays was 79.2%, and FEIA showed higher sensitivity.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…ANA-positivity can be determined by a number of methods, and more recently testing ANA1 subjects by various ANA assays has identified discordant results. [42][43][44] To aid in interpretation and future discussion, we assessed our subjects by 3 different methods (BioPlex, ELISA, and IIF) with all subjects ANA1 by BioPlex and 1 other method, with exception of 1 RNP1 AA individual who was only positive by BioPlex (specificity was confirmed by INNO-LIA [Innogenetics NV, Belgium]). The discordance of ANA testing results has led to questions of whether healthy subjects with BioPlex ANA-positivity, which is a specific indicator for RNA-and DNA-specific autoantibodies common to rheumatic diseases, but who are IIF2 false positives or subjects captured early in the disease process.…”
Section: Discussionmentioning
confidence: 99%